The relation between radiographic manifestation and clinical characteristics of congenital radioulnar synostosis in children: A retrospective study from multiple centers - Pan Hong; Wei Tan; Wei-Zheng Zhou; Yu Zheng; Jin Li; PengFei Zheng; Xin Tang (Frontiers Media S.A., 2023)
ObjectiveTo review the radiographic manifestation and clinical appearance of children with congenital radioulnar synostosis (CRUS) retrospectively.Study designRetrospective cohort study of children with CRUS from multiple medical centers.ResultsA total of 329 patients (male 259, female 70) with an average age of 5.4 years (0.5-16 years old), were included in this study. In particular, 145 patients (145/329, 44.1%) demonstrated bilateral involvement, and 184 patients (left 123, right 61) demonstrated unilateral involvement. As for Clear and Omery (C&O) classification, most patients belonged to Type III, and then followed by Type IV. As for Chinese Multi-center Pediatric Orthopedic Study Group (CMPOS) classification, most patients belonged to Type III, and then followed by Type II and Type I. In C&O Type III, 92.03% patients demonstrated severe pronation. According to CMPOS classification, 92.98% Type I patients demonstrated neutral to mild pronation, 72.17% Type II patients demonstrated moderate pronation, and 92.03% Type III patients demonstrated severe pronation. The age distribution showed no significant difference between C&O Type II and IV (P = 0.96); the pronation ankylosis severity showed no significant difference between C&O Type II and IV (P = 0.387).ConclusionAlthough CRUS is a rare forearm deformity, there are certain relation between radiographic manifestation and clinical forearm functional restriction. CRUS patients of C&O or CMPOS Type III classification might suffer severe pronation deformity and warrant early intervention.